The Effect Of Arm Power, Eye Coordination Through Waist Muscle Flexibility On The Ability To Swim In 50 M Breaststroke For Junior Swimming Athletes - Syaputra, Irfan; Neldi, Hendri (DEPARTEMEN KESEHATAN DAN REKREASI FAKULTAS ILMU KEOLAHRAGAAN, 2024)
The problem in this study is that the breaststroke swimming ability of junior athletes in the city of Bukittinggi still looks stiff and underpowered. The purpose of this study was to determine the effect of arm muscle power, ankle coordination through flexibility on the breaststroke swimming ability of junior athletes in the city of Bukittinggi. This type of research is quantitative, namely casual comparative using path analysis techniques. This research was conducted from January to February 2021 in the swimming pool in the city of Bukittinggi. The population in this study were all junior swimming athletes in the city of Bukittinggi, totaling 32 people. The sampling technique used total sampling technique, so the number of samples in this study were 32 athletes. The instruments in this study were: 1) Arm muscle endurance test by carrying out the Pull-Up test, 2) Eye Coordination Using the Mitcel Soccer Test, Hip Muscle Flexibility Using the Sit and Reach Test, 4) The Ability to Swim in the Breaststroke 50 M. Technique data analysis using statistical path analysis or path analysis. The results of this study are: 1) Arm muscle power has a direct and significant effect on the 50 M breaststroke swimming ability of 12.96%. 2) Coordination of the ankles has a direct and significant effect on the 50 M Breaststroke swimming ability of 12.18%. 3) Waist muscle flexibility has a direct and significant effect on the 50 M Breaststroke Swimming Ability by 8.82%. 4) Arm Muscle Power has an indirect effect on the Ability to Swim 50 M Breaststroke through Waist Muscle Flexibility by 20.61%. 5) Coordination of the ankles has an indirect effect on the ability to swim 50 m breaststroke through waist muscle flexibility by 15.13%. 6) Arm muscle power, ankle coordination and waist muscle flexibility have a simultaneous effect on the 50 M breaststroke swimming ability by 80.80%.